Composition Heterogeneity of Xenoliths of Mantle Peridotites from Alkaline Basalts of the Sverre Volcano, the Svalbard Archipelago - S. G. Skublov; D. S. Ashikhmin (Записки Горного института, 2019)
The article presents the results of a study of the composition of xenoliths of mantle peridotites (seven samples), collected from the Quaternary basalts of the Sverre volcano, the Svalbard archipelago. The presence of two big (more than 15 cm in diameter) xenoliths of spinel lherzolite allowed us to consider a change in their composition in the cen- tral, intermediate, and marginal parts of the samples.